2022
DOI: 10.46471/gigabyte.42
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-scale assembly of the highly heterozygous genome of red clover (Trifolium pratense L.), an allogamous forage crop species

Abstract: Relative to other crops, red clover (Trifolium pratense L.) has various favorable traits making it an ideal forage crop. Conventional breeding has improved varieties, but modern genomic methods could accelerate progress and facilitate gene discovery. Existing short-read-based genome assemblies of the ∼420 megabase pair (Mbp) genome are fragmented into >135,000 contigs, with numerous order and orientation errors within scaffolds, probably associated with the plant's biology, which displays gametophytic self-inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The graphics were performed using Rscript. Note that a recent high-quality assembly of the T. pratense genome (ARS_RCv1.1; Bickhart et al., 2022 ) was not used in this analysis as it has yet to be annotated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The graphics were performed using Rscript. Note that a recent high-quality assembly of the T. pratense genome (ARS_RCv1.1; Bickhart et al., 2022 ) was not used in this analysis as it has yet to be annotated.…”
Section: Methodsmentioning
confidence: 99%
“…Macrosynteny between T. subterraneum , and T. pratense , T. repens , M. truncatula , and L. japonicas was investigated based on homologous translated protein sequences using BLAST searches with an E-value cut-off of 1E-100. For this macrosyntenic analysis, a recent high-quality T. pratense assembly (ARS_RCv1.1; Bickhart et al., 2022 ) was used. As T. repens is an allotetraploid, the two subgenomes were merged into single consensus homoeologous groups, hence eight chromosomes rather than 16.…”
Section: Methodsmentioning
confidence: 99%
“…To test Mabs, I performed a literature analysis and compiled a set of 5 species for which authors reported a high number of haplotypic duplications: Trifolium pratense (Bickhart et al , 2022), Manihot esculenta (Qi et al , 2022), Myripristis murdjan (Guan et al , 2020; Rhie et al , 2021), Adineta vaga (Guiglielmoni et al , 2021), Mytilus coruscus (Li et al , 2020; Sun et al , 2021). In addition, I used Heracleum sosnowskyi , which I studied personally and which also had a lot of haplotypic duplications (preprint to be uploaded to BioRxiv in 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Raw reads were filtered to remove reads less than 30 bases and then mapped to the red clover genome assembly (version ARS_RC1.1; GenBank Accession No. GCA_020283565.1) [ 25 ] using the RNA-Seq tool, CLC Genomics Workbench (v22.0; CLC Genomics Workbench, Qiagen Aarhus A/S, Denmark). Minimum length fraction was set to 0.5 and minimum similarity fraction set to 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular work on red clover has lagged behind many other cultivated crop species despite its relatively small genome [ 20 ], primarily due to the fact that it is an outcrossing species making genetic gains more difficult [ 21 ]. Genomic resources have been developed that now allow for molecular characterization and analysis [ 22 , 23 , 24 , 25 , 26 ]. The high heterozygosity in red clover, while complicating the assembly of contiguous chromosome molecules, has allowed for the identification of chromosomal regions and genes involved in various functions using single nucleotide polymorphic loci (SNPs) mapping [ 26 , 27 , 28 , 29 , 30 ], including identification of red clover genotypes differing in their nitrogen fixation potential [ 31 ].…”
Section: Introductionmentioning
confidence: 99%